Comparing Papanicolaou test results obtained during pregnancy and post‐partum. Issue 4 (27th January 2017) - Suzuki, Kazuhiro; Furuhashi, Madoka; Kawamura, Takuya; Kubo, Michiko; Osato, Kazuhiro; Yamawaki, Takaharu
Abstract: Aim: Cervical cancer onset initially occurs during youth. Papanicolaou tests performed in early pregnancy can detect cervical cancer; however, Papanicolaou tests during pregnancy have been noted to be inaccurate, reflecting changes associated with pregnancy. Therefore, we assessed the effect of pregnancy on Papanicolaou test results. Methods: Of 1351 pregnant women who delivered at Ise Red Cross Hospital between January 2010 and December 2014, 1213 underwent Papanicolaou tests at early pregnancy and post‐partum. We compared the Papanicolaou test results. Results: The results of the Papanicolaou test were different in 32 patients. Of the 1191 patients negative for intraepithelial lesions or malignancy in early pregnancy, 16 had other cytological abnormalities post‐partum. We performed therapeutic conization post‐partum in four patients. The Papanicolaou test results in early pregnancy of the four patients were negative for intraepithelial lesions or malignancy in one patient, atypical squamous cells of undetermined significance in one and high‐grade squamous intraepithelial lesion in two. Conclusion: The results of the Papanicolaou test during pregnancy may not be accurate because of the influence of hormones associated with pregnancy. Taking advantage of the one‐month post‐partum screening visit can lead to early detection and treatment of cervical cancer in young people.